INTRODUKSI EKOWISATA SEVE (SUKAMADE ENCLAVE VILLAGE ECOTOURISM) KAWASAN TAMAN NASIONAL MERU BETIRI BANYUWANGI - Kuntadi, Ebban Bagus; Sunartomo, Aryo Fajar; Subaharianto, Andang; Budiman, Subhan Arif; ihsannudin, ihsannudin; Luthfiyah, Lenny; Avenido, Cheska Andrea C; Panapanaan, Ansherine M (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
Sukamade is one of the hamlets in Sarongan Village, Pesanggaran District, Banyuwangi Regency. Sukamade is an enclave village or a village that is spatially concentrated in the middle of the TNMB forest area and the community has a high dependence on the TNMB forest environment. The Sukamade community has economic, social and cultural vulnerabilities. This condition needs to be paid concern to by providing access to utilize the potential for ecotourism activities in Sukamade. Hopefully, the community will gain motivation to participate in conservation activities (community-based conservation). Pokmas PPA as one of the elements of society in Sukamade is introduced into Sukamade Enclave Village Ecotourism (SEVE). In order to accomplish SEVE, it is necessary to (a) strengthen the institutional capacity of Pokmas PPA; (b) Strengthening ecotourism knowledge and skills of Pokmas PPA members; (c) Strengthening ecotourism attractions; and D). Strengthening information and promotion media through social media. Institutional strengthening is carried out through training and assistance in the issuance of AD/ART, SOP, legality of notary deeds/AHU Kemenkumham, NPWP and bank accounts in the name of Pokmas PPA. The efforts to strengthen ecotourism knowledge and skills also need to be carried out in Pokmas PPA related to safety, services and interpretation-education. Strengthening ecotourism attractions is the basis for SEVE's introduction through the riverside coffee and jungle track attractions. Delivery of information and promotion of Pokmas PPA activities is carried out by providing training and assistance in creating and filling content for Facebook, Instagram, TikTok and YouTube accounts.